Exploring Age and Gender Influences on Consumer Behaviour in Online Food Delivery Services - Zaveri, Krish; Thacker, Nevil; Patel, Suhani; Meghwal, Mayank; Chauhan, Rahul; Maseleno, Andino; Raisa, Kharchenko (Dinasti Publisher, 2025)
This study examines the demographics and behaviours of online food delivery service users in Ahmedabad, focusing on age and gender influences. Data from 99 respondents reveal a predominance of young male users, with significant findings indicating that age affects the frequency of service use and satisfaction with issue resolution. Conversely, gender shows no significant impact on usage patterns or customer experiences. The analysis highlights the importance of tailoring marketing strategies to target different age groups while emphasizing universal improvements in service quality. Future research could explore additional demographic factors and regional variations, contributing to a broader understanding of consumer behaviour in the global online food delivery market. These insights are essential for enhancing customer satisfaction and driving growth in this evolving industry.